Live coding and teaching SuperCollider. Issue 1 (1st May 2016) - Collins, Nick
SuperCollider (SC) is a highly customizable programming language for music; live coding is the dynamic rewriting of a computer program as a concert or exploratory act. Learning sessions on SC can make ready use of live coding techniques, with many interesting musical possibilities, and this article explores the author's twelve years of SC teaching. Contexts include SC workshops for adults, undergraduate computer music classes, and widening participation of creative coding sampler sessions for 11–13-year olds. The article is a personal reflection on pedagogy, which can provide ideas for live coding and computer music teaching across a range of audiences.